2018
DOI: 10.1037/sgd0000297
|View full text |Cite
|
Sign up to set email alerts
|

Motivational interviewing with couples: A theoretical framework for clinical practice illustrated in substance use and HIV prevention intervention with gay male couples.

Abstract: Epidemiological data indicate the need to address substance use and sexual HIV transmission risk among gay and bisexual men in relationships. While brief Motivational Interviewing (MI) delivered to the individual has shown efficacy in reducing sexual HIV risk with casual partners and substance use, the application of MI with couples has received less attention. Most studies of MI with couples have conceptualized the “spouse” or partner as an adjunct participant in the treatment of an identified client. We prop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
28
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 19 publications
(32 citation statements)
references
References 62 publications
(103 reference statements)
4
28
0
Order By: Relevance
“…Earlier research indicated that 35-68% of new HIV infections among SMM were transmitted between main partners [4][5][6]. Estimated rates were as high as 79% among younger SMM (aged [18][19][20][21][22][23][24][25][26][27][28][29] [6]. More recent research has indicated that the likelihood of having condomless anal sex (CAS) with casual partners is comparable for single SMM and partnered SMM in non-monogamous sexual agreements [7,8].…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…Earlier research indicated that 35-68% of new HIV infections among SMM were transmitted between main partners [4][5][6]. Estimated rates were as high as 79% among younger SMM (aged [18][19][20][21][22][23][24][25][26][27][28][29] [6]. More recent research has indicated that the likelihood of having condomless anal sex (CAS) with casual partners is comparable for single SMM and partnered SMM in non-monogamous sexual agreements [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…To address this challenge, Starks et al [28,29] drew on Interdependence Theory [30,31] to derive processes and techniques unique to implementing MI with couples. This work adopted the novel premise that the couple was "the client" rather than identifying one partner in the couple as "the client" and the other as an "adjunct participant."…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations